PENGARUH PRODUKSI TANAMAN PANGAN TERHADAP INDEKS HARGA PANGAN DI KOTA MANADO - Sylvia S Manaida; Esry O.H. Laoh; Olfie L.S. Benu; Joachim N.K. Dumais (COCOS, 2013)
ABSTRACTThe objective of this study in to determine the effect to Crop Production OfFood Price Index in Manado this study uses secondary data. The data used is obtainedfrom the Office of the Central Bureau of Statistics of North Sulawesi Province, in theform of time series data. Analysis of data using multiple linear regressi on models toexamine the relationship between production of food crops, with food price indeks inManado city.The results of research showed that the effect of Crop Production Of Food PriceIndex in Manado City is influenced by two variables, the production of food crops inthe city of Manado and food crop production in North Sulawesi Province outside ofthe city of Manado.Based on regression analysis, it can be concluded that the F-value equal to 2,07with a significant level of 0,197 which means the production of food crops in the cityof Manado and food crop production in North Sulawesi city of Manado out jointlysignificant effect on food price index. Determinant coefficient ( ) of 0,521 indicatedthat 52.1% of food price index is affected by the variables the production of foodcrops in the city of Manado and food crop production in North Sulawesi Provinceoutside of the city of Manado. Regression coefficient for the variable crop productionin the city of Manado was positive it means that the variable is 0,07058 cropproduction in Manado City but had a significant effect on food price index withP=0,092, but the regression coefficient for the variable crop production in NorthSulawesi Province outside of the city of Manado -0,0003927 was negative whichmeans variable crop production in North Sulawesi Province outside of the city ofManado had a significant effect on food price index in the city of Manado withP=0,090.